2016
DOI: 10.1001/jamafacial.2015.2251
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Rhinoplasty Using Multiplanar Carved Costal Cartilage

Abstract: IMPORTANCE Reconstructive rhinoplasty often requires the use of cartilage grafts. Full-thickness autologous costal cartilage grafts provide a large amount of cartilage in a single uncarved block and are often used for major reconstructions. Warping is frequently described as a complication of rib cartilage use in rhinoplasty.OBJECTIVE To describe an approach to cartilage carving whereby a single block of cartilage is carved in a multiplanar manner to mimic or redefine the anatomic relationships and resist warp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These studies comprised 1041 patients of whom 741 received autologous grafts and 293 received IHCC grafts. Studies were published between January 1, 1990, and December 31, 2017; the mean sample size was 36 patients (range, 9-157 patients); and studies were from countries around the world, including Turkey (n = 9), 3,[23][24][25][26][27][28][29][30] the United States (n = 5), 9,13,[31][32][33] South Korea (n = 4), 14,18,19,34 Italy (n = 2), 35,36 India (n = 2), 37,38 the United Kingdom (n = 1), 39 Germany (n = 1), 40 the Netherlands (n = 1), 15 Egypt (n = 1), 41 South Africa (n = 1), 42 and Saudi Arabia (n = 1). 43 Mean follow-up time ranged from 6 to 48 months in the studies that reported follow-up, although 8 studies did not.…”
Section: Resultsmentioning
confidence: 99%
“…These studies comprised 1041 patients of whom 741 received autologous grafts and 293 received IHCC grafts. Studies were published between January 1, 1990, and December 31, 2017; the mean sample size was 36 patients (range, 9-157 patients); and studies were from countries around the world, including Turkey (n = 9), 3,[23][24][25][26][27][28][29][30] the United States (n = 5), 9,13,[31][32][33] South Korea (n = 4), 14,18,19,34 Italy (n = 2), 35,36 India (n = 2), 37,38 the United Kingdom (n = 1), 39 Germany (n = 1), 40 the Netherlands (n = 1), 15 Egypt (n = 1), 41 South Africa (n = 1), 42 and Saudi Arabia (n = 1). 43 Mean follow-up time ranged from 6 to 48 months in the studies that reported follow-up, although 8 studies did not.…”
Section: Resultsmentioning
confidence: 99%
“…Gibson and Davis first reported on the principle of the balanced section, cutting the cartilage in such a way that the intrinsic oppositional forces are in equilibrium, causing them to be neutralized. Since then, many other authors have tried to refine this principle to further reduce the amount of warp or the operative morbidity . Studies have also been performed to evaluate whether the level of rib, orientation of the balanced section, or storage conditions of the graft affect warpage: none had a significant effect.…”
Section: Introductionmentioning
confidence: 99%
“…As regard rib cartilage, it has many drawbacks such as learning curve is needed, pneumothorax may occur, and asymmetry of chest wall can present [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%